Diagnostic Value of D-Dimer and INR in Patients Suspected to Have Prosthetic Valve Dysfunction - Moghadam,Reza Heidari (2022)
ABSTRACT Introduction: Prosthetic valve dysfunction is a potentially critical complication of heart valve replacement. An easy and quickly applicable diagnostic procedure is required for recognizing the prosthetic valve dysfunction. The purpose of this study was to prospectively define the diagnostic value of D-dimer and INR level in predicting prosthetic valve dysfunction. Methods: This cross-sectional study was performed in 70 patients suspected to have prosthetic valve dysfunction admitted to Imam Ali Hospital, affiliated with Kermanshah University of Medical Sciences (KUMS), Kermanshah Province, Iran. Cinefluoroscopy, as the gold standard diagnostic test, was used for the diagnosis of prosthetic valve dysfunction in enrolled patients. Two milliliters of blood from each patient were taken into a tube containing sodium citrate anticoagulant. To evaluate D-dimer, the cutoff value was set at 500 ng/ml. Also, to evaluate international normalized ratio (INR), the cutoff value was set at 2. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (PLR), and negative likelihood ratio (NLR) of the serum markers were used to describe predictive properties. Results: Of 70 patients, 27 (38.6%) were male and 43 (61.4%) were female, and the mean age was 54.67±15.11 years (range, 18 to 80 years). Of 70 patients, 27 (38.6%) had prosthetic heart valve malfunction demonstrable by fluoroscopy, and 19 patients (27.1%) had D-dimer levels >500 ng/ml. Elevated D-dimer levels (>500 ng/ml) have been indicated to have sensitivity of 70.4%, and hence an NPV of 84.3%, specificity of 100%, PPV of 100%, NLR of 0.3, and the infinity value of PLR for predicting prosthetic valve dysfunction. There was a significant relationship between fluoroscopy and D-dimer test (P=0.001). A kappa coefficient value of 0.745 indicated a substantial agreement between D-dimer and fluoroscopy testing. Mixing test (combination of D-dimer and INR) showed to have 100% sensitivity, and hence a NPV of 69.8%, specificity of 69.8%, PPV of 51.8%, NLR of 1.41, and PLR of 1.44 for predicting prosthetic valve dysfunction. Conclusion: D-dimer with moderate sensitivity and high specificity is an ideal marker for the diagnosis of prosthetic valve dysfunction in suspected patients. Enhanced plasma D-dimer level is not by itself diagnostic of a prosthetic valve dysfunction but may alert physicians to refer the patient for more detailed examination, preferably by fluoroscopy. Mixing test with 100% sensitivity can apply as a rule-out test.